Hieracia balcanica XIV. Two new species in Hieracium sect. Cernua (Asteraceae) from Bulgaria - Szeląg, Zbigniew (Phytotaxa, 2018)
Two apomictic, polyploid (x=9) species in Hieracium sect. Cernua are described from Bulgaria, and illustrated with photos of the holotypes. These are H. gussevii (3x) from the Vitosha Mountains, which combines the morphological features of H. sparsum and H. robustum, and H. vladimirovii (4x) from the Stara Planina Mountains, of presumably hybrid origin between H. cernuum and H. olympicum.